1995
DOI: 10.1002/ange.19951072234
|View full text |Cite
|
Sign up to set email alerts
|

Kommensurables Einfrieren von n‐Alkanen im Silicalit

Abstract: Ein überraschendes Verhalten bei der Desorption aus Silicalit zeigen von den n‐Alkanen mit vier bis zehn C‐Atomen n‐Hexan und n‐Heptan. Während die längeren und kürzeren n‐Alkane in einem Schritt desorbieren, ist die Desorption von n‐Hexan und n‐Heptan zweistufig. Diese Ergebnisse können durch ein kommensurables Einfrieren erklärt werden, ein Phänomen, das kürzlich anhand der Ergebnisse von Computersimulationen vorausgesagt wurde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Experimentally, it is found that, from C 14 to C 22 , the number of −CH x groups adsorbed per unit cell remains at a constant value of 53−54. Some older studies report adsorption capacities of 51−52 −CH x groups adsorbed per unit cell for C 7 3,19 and for C 10 , obtained with gas-phase adsorption measurements. A particular study reports a value of even 55.3 −CH x groups adsorbed per unit cell for C 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, it is found that, from C 14 to C 22 , the number of −CH x groups adsorbed per unit cell remains at a constant value of 53−54. Some older studies report adsorption capacities of 51−52 −CH x groups adsorbed per unit cell for C 7 3,19 and for C 10 , obtained with gas-phase adsorption measurements. A particular study reports a value of even 55.3 −CH x groups adsorbed per unit cell for C 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, it is found that the adsorption capacity, expressed in molecules adsorbed per unit cell, decreases with carbon number. A steep drop in adsorption capacity is observed between C 6 and C 8 . ,, The most probable explanation for this less efficient packing of C 7 and C 8 molecules compared to shorter ones is that C 6 molecules fit nicely within the sinusoidal channel segment, while longer molecules protrude into the intersections and thus partially obstruct filling of adjacent sections . No attention has been paid in the literature to the packing of long-chain alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…The excess of sorbate was used in order to ensured that the maximum loading (8 molecules/u.c. ) was achieved. The Silicalite-I/ n- hexane mixture was kept in a sealed glass tube at 353 K for 6 h. Thermogravimetric measurements were carried out heating the sample up to 650 K in a Linseis L81/075 thermobalance to verify the loading.…”
Section: Methodsmentioning
confidence: 96%
“…It is most probable that the presence of aluminium is responsible for the difference. (It has been found that the heats of adsorption of n -pentane and n -hexane in ZSM-5silicalite with framework aluminiumare increased by some 10 kJ/mol compared to silicalite …”
Section: Energetics Of N-alkane Sorptionmentioning
confidence: 99%